Simulation of Speed Control on a PMSM Using a PI Controller - Widagdo, Reza Sarwo; Hariadi, Balok; Wardah, Izzah Aula (Jambura Journal of Electrical and Electronics Engineering, 2024)
In order to manage the speed of a permanent magnet synchronous motor drive system, a practical approach for a PI controller has been developed and put into practice in this study. The adopted approach, which also preserves the proportional integral controller's straightforward structure and features, significantly enhanced the performance of the prior proportional integral controller. The final PI controller delivers quick and precise response, strong noise rejection, and minimal sensitivity to permanent magnet synchronous motor parameter fluctuations. The findings demonstrate that the suggested controller may provide best performance in terms of accuracy, parametric variation, and load torque disturbance when entering a proportional value of 0,013 and an integral value of 16,61. The proposed method has been exhaustively tested under various circumstances. The proposed solution not only possesses attributes like simplicity and ease of implementation for real-time, but also stability and effectiveness.